2017
DOI: 10.1002/eap.1512
|View full text |Cite
|
Sign up to set email alerts
|

Patterns in Greater Sage‐grouse population dynamics correspond with public grazing records at broad scales

Abstract: Human land use, such as livestock grazing, can have profound yet varied effects on wildlife interacting within common ecosystems, yet our understanding of land-use effects is often generalized from short-term, local studies that may not correspond with trends at broader scales. Here we used public land records to characterize livestock grazing across Wyoming, USA, and we used Greater Sage-grouse (Centrocercus urophasianus) as a model organism to evaluate responses to livestock management. With annual counts of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
29
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 65 publications
0
29
0
Order By: Relevance
“…Although we observed negligible or null effects of SGI‐RGS on bare ground, litter, and herbaceous cover, these and other indicators of rangeland health may respond differently to grazing management treatments in regions differing in climate, vegetation community composition, and evolutionary history of grazing such as the Great Basin (Mack and Thompson ). Recently, Monroe et al () reported population‐level responses of sage‐grouse to timing of grazing interacted with primary productivity in Wyoming, such that negative responses to early season grazing were not evident in highly productive regions. Our finding of a lack of response to variation in grazing management or rest is consistent with this pattern because our study area was productive relative to sage‐grouse habitat in Wyoming.…”
Section: Discussionmentioning
confidence: 99%
“…Although we observed negligible or null effects of SGI‐RGS on bare ground, litter, and herbaceous cover, these and other indicators of rangeland health may respond differently to grazing management treatments in regions differing in climate, vegetation community composition, and evolutionary history of grazing such as the Great Basin (Mack and Thompson ). Recently, Monroe et al () reported population‐level responses of sage‐grouse to timing of grazing interacted with primary productivity in Wyoming, such that negative responses to early season grazing were not evident in highly productive regions. Our finding of a lack of response to variation in grazing management or rest is consistent with this pattern because our study area was productive relative to sage‐grouse habitat in Wyoming.…”
Section: Discussionmentioning
confidence: 99%
“…, Monroe et al. ). In addition to their loss of resolution, average‐based approaches can be biased due to the 0‐bounded, 0‐inflated, non‐normal distribution of density and non‐uniform sampling effort, which may obscure the impact of environmental covariates on the underlying density (Robinson et al.…”
Section: Discussionmentioning
confidence: 98%
“…, Monroe et al. ). In estuarine systems, for example, freshwater flow influences habitat quality and quantity (Robins et al.…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…Although we simulated constant rates of annual lek attendance (p s ) across leks and years, attendance may vary systematically and could bias trend estimates from lek counts (Blomberg et al 2013). For example, density dependence was previously estimated using peak counts (Garton et al 2011, Monroe et al 2017, Edmunds et al 2018), but attendance also may be density-dependent (Blomberg et al 2013) and could confound estimates of density dependence ink. Similarly, cumulative winter precipitation influences soil moisture and productivity of semi-arid ecosystems dominated by sagebrush (Artemisia spp.…”
Section: Discussionmentioning
confidence: 99%